Muon-spin relaxation and density functional techniques in the study of novel magnetic systems - Lang, F (2017)
The main focus of this thesis is the experimental muon-spin relaxation technique (μ+SR) and its application to study novel and unconventional magnetic behaviour. I present a range of experimental measurements which I supplement with theoretical calculations to remove the two main limitations inherent toμ+SR and thereby improve the understanding of the experimentally observed behaviour. Additionally, I investigate the potential effects of demagnetising fields on highfield μ+SR measurements. μ+SR employs positively charged muons as sensitive local magnetic probes but has the essential drawback that there is normally a lack of knowledge about where the muons implant in a given sample and the extent of subsequent local distortions. In some cases this nescience makes interpretation ofμ+SR data very challenging and severely limits the conclusions that can be drawn. Two research projects presented in this thesis are centred around utilising ab initio structural calculations based on density functional theory in order to remove these two inherent limitations ofμ+SR and gain insights into the stopping sites of the muons and their local environments. In the case of the Pr based pyrochlores Pr2B2O7 (B=Sn, Hf, Zr, Ir) I combine such ab initio computations of the muon sites with calculations of the crystalfield levels of the Pr3+ ions. I demonstrate that the non-Kramers doublet ground state of the Pr ions is split due to the presence of the muons and that this consequently results in a hyperfine enhancement of the Pr nuclear moments. By showing the theoretically calculated values of the ground state splittings to be in fair agreement with those obtained from fits to the experimental data, I demonstrate that theμ+SR measurements of Pr2B2O7 re ect muon induced effects rather than intrinsic behaviour. I subsequently investigate the conceptually very similar spin ices A2Ti2O7 (A= Dy, Ho) using the same methodology and confirm that in this case the muons act as passive probes. A second project presented in this thesis concerns the compound α-RuCl3, in which Ru ions form nearly perfect two-dimensional honeycomb layers. The experimentalμ+SR data reveal two magnetic phase transitions, the origins of which I study by combining calculations of the potential muon sites with computations of the dipolar fields experienced by the muons at these sites for different magnetic structures. I show that the experimental observations are only fully explained through a temperature regime between the two measured transitions in which the Ru spins share significant correlations within the honeycomb layers but not between the separate layers. A final research aspect I present is a study of the potential effects of demagnetising fields in high fieldμ+SR measurements. I derive an analytical solution for the demagnetising tensor of a uniformly magnetised finite cylinder and use it to show that edge regions of a sample suffer the most from demagnetising effects. I subsequently discuss the resulting experimental signatures and methods to identify and reduce them.